Cost benefit analysis of diversified farming systems across Europe: Incorporating non-market benefits of ecosystem services - Alcon, Francisco; Albaladejo-García, Jose A.; Martínez-García, Victor; Rossi, Eleonora S.; Blasi, Emanuele; Lehtonen, Heikki; Martínez-Paz, Jose M.; Zabala, Jose A. (Elsevier, 2024)
Crop diversification can enhance farm economic sustainability while reducing the negative impact on the environment and ecosystem services related. Despite the market and non-market benefits of crop diversification, monocropping is a widely used dominant practice in Europe. In this context, this works aims to assess the overall economic impact of several crop diversification systems across Europe and compared it to the monocropping system. For this purpose, an economic valuation by integrating market and non-market values for eight case studies distributed across three different European pedoclimatic regions (Southern Mediterranean, Northern Mediterranean and Boreal) is proposed. The economic valuation was conducted both in the short and medium-long term. For the short-term we conducted a social gross margin analysis, while for the medium-long term a cost-benefit analysis is developed. The results show an improvement in social gross margins for most of the diversification scenarios assessed when environmental and socio-cultural benefits are considered in the short-term. In the medium and long-term the transformation of cropping towards a more diversified agriculture is encouraged by greater economic benefits. These results provide a first insight in global economic performance of diversified cropping systems, whose main contribution relies on the integration of market and non-market values of ecosystem services from crop diversification. They are expected to be useful for guiding policy makers to promote crop diversification practices as a key instrument for building resilience in farming systems for an adaptive management to climate change.
Keywords: agriculture; diversification; social gross margins; sustainability; environmental benefits